Changes in dielectric properties of Pb(Zr1/2Ti 1/2)O3-Pb(Co1/3Nb2/3)O3 ceramics under compressive stress applied parallel and perpendicular to electric field - Muangjai Unruan (2018)
The influences of compressive stress on the dielectric properties of (1-x)Pb(Zr1/2Ti1/2)O3-(x)Pb(Co1/3Nb2/3)O3 (x = 0.1-0.5) ceramics were investigated in this study. The dielectric properties were measured under compressive stress applied parallel and perpendicular to an electric field direction. The results clearly showed that the superimposed compression stress had pronounced effects on the dielectric properties of PZT-PCN ceramics. In general, with increasing compressive stress (applied parallel with the electric field direction) the dielectric constant of the ceramics increased, while the dielectric loss tangent decreased. Interestingly, the observed changes of the dielectric properties with the perpendicular compressive stress were opposite to those under the parallel stress. Copyright © Taylor & Francis Group, LLC.